"An all-weather, all-terrain fighter": Subaltern resistance, survival, and death in Mohammed Hanif's Our Lady of Alice Bhatti. (June 2015) - Mirza, Maryam
Victor Li's theory of necroidealism draws our attention to the tendency in literary works and writings by Subaltern Studies historians to romanticize the dead subaltern so that in death he or she emerges as an "exemplary, heroic symbol of resistance". In these works, the "ambiguity of struggle" of the living subaltern contrasts sharply with the idealized heroism of his or her dead counterpart. The eponymous protagonist of Mohammed Hanif's Our Lady of Alice Bhatti is an untouchable, lower-class Christian woman in contemporary Pakistan who is determined to survive and surpass her subaltern status but dies a brutal death, following which her father makes a case for her canonization. This article is an in-depth analysis of the depiction of Alice's multifaceted subalternity and the strategies of resistance that she deploys as well as an evaluation of the portrayal of her death to demonstrate that the novel unequivocally rejects an idealization of both subaltern life and death.